Reputation Life Cycle of The SM Foundation and Customers’ Support - Ibrahim, Muhammad Alishahdani (UI Scholars Hub, 2021)
Reputation is a key construct in organizational sciences since reputation signals its past behavior and its prospect in the future. The purpose of this paper is to explore the development and influence of both personal and organizational reputation and its impact to customer support. The organiza-tion life cycle theory is applied to the “SM” foundation, one of Indonesian largest Islamic social enterprise which experienced fast growth and decline due to the decline of its leader reputation. The case shows that personal reputation of leader is very important in the start-up and early development phase of the organization but it may threaten the organizational sustainability at a later stage when the leader’s personal reputation is conveyed into the organization reputation.